Pengaruh Media Sosial terhadap Komunikasi Interpersonal Remaja dalam Keluarga - Siregar, Dhea Amanda; Harahap, Mickael Halomoan; Harahap, Nursapia (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to determine the impact of using social media on interpersonal communication between teenagers in a family. The research method uses a descriptive method with a qualitative approach, and data collection is based on a literature review and in-depth interviews with parents (father or mother) and children (teenagers). was chosen as the topic. Qualitative data analysis is interactive and takes place from the initial stages of the research until receiving the results. Research shows that the use of social media influences teenagers' interpersonal communication within the family. Teenagers tend to be more focused. This may influence their communication with family members and make them focus more on social media. to reduce interactions with other family members May become insensitive to family situations Therefore, parents should set a good example when communicating with their children, support their children and listen to what their children have to say about problems and worries